Seismic performance of fish-bone shaped buckling-restrained braces with controlled damage process. (15th August 2018) - Jia, Liang-Jiu; Ge, Hanbin; Xiang, Ping; Liu, Yan
Highlights: A novel type of fish-bone shaped buckling-restrained braces with a damage control mechanism are proposed. Post-necking deformation capacity of material can be fully utilized by formation of multiple necks. Interaction of multiple stoppers and restraining components leads to controlled damage process. The proposed BRBs can sustain tensile load even after rupture of the central segment. Optimum design values of the critical parameters determined through cyclic tests on eight specimens. Abstract: A new type of all-steel fish-bone shaped buckling-restrained braces (FB-BRBs) with large maximum ductility and cumulative ductility have been proposed, and their excellent seismic performance and failure mechanism have been verified through a series of experiments in a previous study. The proposed FB-BRBs can fully utilize ductility of a material through a multiple-neck deformation mechanism. This mechanism can achieve a well-controlled damage process of different segments of the FB-BRBs. In addition, the proposed FB-BRBs can sustain tensile load-carrying capacity even after rupture of the core plate, which is owing to the interaction between the multiple stoppers of the core plate and corresponding filling plates. Both experimental and numerical studies have been conducted. However, the previous study failed to achieve the expected failure mechanism due to unexpected failure at the stoppers of the FB-BRBs. This paper aims to experimentally investigate the optimal values of the design parameters of the FB-BRBs, and further clarify the failure mechanism. Quasi-static cyclic loading tests were carried out using eight specimens with different configurations. Different failure modes of the newly proposed FB-BRBs are verified, and high seismic performance of the dampers is proved through the experimental results.